2020
DOI: 10.1007/s40279-020-01411-8
|View full text |Cite|
|
Sign up to set email alerts
|

The Football Association Injury and Illness Surveillance Study: The Incidence, Burden and Severity of Injuries and Illness in Men’s and Women’s International Football

Abstract: Objectives To determine the incidence and characteristics of injury and illness in English men’s and women’s senior and youth international football. Methods Time-loss injuries and illnesses, alongside match and training exposure, were collected across 8 seasons (2012–2020) in youth (U15, U16, U17, U18, U19) and senior (U20, U21, U23, senior) English men’s and women’s international teams. Analysis of incidence, burden, and severity of injury and illness wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 58 publications
3
50
0
Order By: Relevance
“…Another study performed among female first division female football players reported a similar match injury incidence (19.0 per 1000 h) but a slightly lower number of injuries during training exposures (1.7 per 1000 h) [10]. Regarding injury burden, the results in the present research are partially in accordance with those previously reported in the literature by Sprouse et al [63]. While the authors reported injury burdens of 538.1 and 69.6 days of absence due to injury per 1000 h exposure to matches and training, respectively, among senior English international female football players, we found in the present investigation similar training (63.4 vs. 69.6) but greater match injury burden recordings (1440 vs. 538.1).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Another study performed among female first division female football players reported a similar match injury incidence (19.0 per 1000 h) but a slightly lower number of injuries during training exposures (1.7 per 1000 h) [10]. Regarding injury burden, the results in the present research are partially in accordance with those previously reported in the literature by Sprouse et al [63]. While the authors reported injury burdens of 538.1 and 69.6 days of absence due to injury per 1000 h exposure to matches and training, respectively, among senior English international female football players, we found in the present investigation similar training (63.4 vs. 69.6) but greater match injury burden recordings (1440 vs. 538.1).…”
Section: Discussionsupporting
confidence: 92%
“…Currently, there is a growing body of knowledge with respect to injury incidence descriptions among female football players [2,5,63,64]. It is known that female players suffer from a lower injury incidence but a greater injury burden due to their increased risk for severe articular injuries such as anterior cruciate ligament (ACL) rupture [1].…”
Section: Discussionmentioning
confidence: 99%
“…In our opinion, this can be considered as a logical response to the difference between the amount of exposure. Sprouse et al have also reported match exposure to be a risk factor for these injuries in women's international soccer 28 …”
Section: Discussionmentioning
confidence: 98%
“…Football is the most common type of sports worldwide and is associated with a high incidence of injuries [1,2]. Many studies have analysed injury patterns with regard to the different activity levels or training vs. match [1][2][3]. Overall, professional football players have a high risk of sustaining injuries [1,4].…”
Section: Introductionmentioning
confidence: 99%
“…Overall, professional football players have a high risk of sustaining injuries [ 1 , 4 ]. Most injuries occur during matches and affect the lower extremities [ 1 , 3 , 5 , 6 ]. Besides the consecutive time loss [ 7 ], the negative effect on team performance [ 5 ], and the possible long-term consequences, such as an increased risk of osteoarthritis [ 8 ], football-related injuries may influence a player’s career and quality of life [ 5 ].…”
Section: Introductionmentioning
confidence: 99%